WAY OF ACCELERATION OF DEVELOPMENT OF OIL AND GAS DEPOSITS OF THE UKRAINIAN SHELF OF BLACK AND AQUATORIUM OF AZOV SEAS - Яремійчук, Роман Семенович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Suggestions in relation to the ways of acceleration of development of Oil and Gas deposits of the Ukrainian shelf of Black and aquatorium of Azov seas are laid out seas, prepared by the group of specialists by direction of professor R.Yaremiychuc.